The threat environment of the UK and Scotland in the context of the UK National Security Strategy : report on the second of six events in the seminar series: Security in Scotland, with or without constitutional change /: report on the second of six events in the seminar series: Security in Scotland, with or without constitutional change. ([2014?]) - Unknown
No abstract available